Assessment of liquid captopril formulations used in children. Issue 3 (27th October 2010) - Mulla, H; Hussain, N; Tanna, S; Lawson, G; Manktelow, B N; Tuleu, C; Samani, N J; Pandya, H C
Abstract : Objective: Unlicensed liquid captopril formulations are commonly used to treat children with heart disease. This study assessed the bioequivalence of two liquid preparations against a licensed tablet form. Design: An open label, single dose, three-treatment, three-period, crossover trial. Setting: Outpatient. Patients: Healthy adult volunteers (n=18). Interventions: Each subject was randomly assigned to one of six dosing sequences, and dosed with 25 mg captopril on each of three dosing visits separated by a washout of at least 14 days. Blood samples for pharmacokinetic analysis were taken at regular intervals (0 min to 10 h) post-dose. Main outcome measures: Bioequivalence of the formulations would be concluded if the 90% CI for the estimated ratio of the means of Cmax (maximum plasma concentrations) and area under curve(AUC) (extent of absorption) lay entirely within the range 0.8 to 1.25 Results: Both liquid formulations failed the bioequivalence assessment with respect to Cmax and AUC. The 90% CI of the mean ratios of liquid/licensed tablet for both Cmax and AUC, fell outside the 0.8 to 1.25 limits. There was also considerable within-subject variability in Cmax (97.5%) and AUC (78.5%). Conclusions: Unlicensed captopril formulations are not bioequivalent to the licensed tablet form, or to each other, and so cannot be assumed to behave similarly in therapeutic use. Thus formulation substitution must be done with care and may require a period of increased monitoring of the patient. There is also significant within-subject variability in performance which has clinical implications with respect to titrating to an optimum therapeutic dose.